PERANCANGAN LOCK HIDROLIK TIPPLER DI PT. HASNUR CITRA TERPADU - , NOER FAJAR PRADANA, Ir. Bambang Suharnadi, MT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
When the reversal process in a rotet of 360 lorry on Tippler will move on the rail hovering over it with the lock that rested on passive or stop. In other avoid unligment on lorry wheels, it needed a part that could lock the active state so the lorry remain on the track, even though behind the rail until one rotation it will not have a resistant. The objective of this study is to design a tool that can lock the lorry an in progres place study when using Tippler, so that the wheels of the lorry will not shifted on its rails. The method akont in this study are derdided in several step. First is Literature. Second observe the processing line. Third design the tool mechanisme. Fourth calculate the draft designed. Fifth redesign. With hydraulic lock on the Tippler is expected the draft plan unshift on it is wheels of the lorry, theraf one the tippler can optimally operate.finally no task delay.